Cathode–Sulfide Solid Electrolyte Interfacial Instability: Challenges and Solutions - Brahmbhatt, Teerth; Yang, Guang; Self, Ethan; Nanda, Jagjit (Frontiers in Energy Research, 2020)
All-solid-state batteries are a candidate for next-generation energy-storage devices due to potential improvements in energy density and safety compared to current battery technologies. Due to their high ionic conductivity and potential scalability through slurry processing routes, sulfide solid-state electrolytes are promising to replace traditional liquid electrolytes and enable All-solid-state batteries, but stability of cathode-sulfide solid-state electrolytes interfaces requires further improvement. Herein we review common issues encountered at cathode-sulfide SE interfaces and strategies to alleviate these issues.